Pengaruh Keragaman Produk, Kualitas Layanan dan Citra Perusahaan terhadap Loyalitas Nasabah PT. BPR Bunga Sutra Mas Tabanan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of product diversity, service quality, and corporate image on customer loyalty at PT. BPR Bunga Sutra Mas Tabanan. The research is motivated by the intense competition in the banking sector, which requires PT. BPR Bunga Sutra Mas Tabanan to enhance its competitiveness through product development, superior service, and a strong corporate image. A quantitative approach was used, with data collected through questionnaires distributed to 180 priority customers. The data were analyzed using multiple linear regression. The results indicate that product diversity and service quality have a positive and significant effect on customer loyalty. However, corporate image does not have a significant effect on customer loyalty. These findings imply that enhancing product variety and providing high-quality service are key factors in building customer loyalty, while the effectiveness of corporate image in this context may need to be re-evaluated.